Age Features of Own Greed Determination and Its Assessment in Other - Yanovskaya, Svitlana; Turenko, Rimma; Kononenko, Nelli; Bilous, Natalia; Zakutnya, Inna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2022)
Greed is one of the most common features in human nature, and it has recently attracted increasing research interest. The purpose of this work is to study the age-specific characteristics of determining own greed and its evaluation in others. We continue our research on greed as a personal trait, the presence of which leads to the maximum satisfaction of our own interests, at the expense of the well-being of others or as a result ignoring their needs. The problem of greed gained momentum with the advent of the Covid-19 pandemic, people of all ages and social status were forced to redistribute their material and intangible resources, save and save,when the others, on the contrary, increased their wealth through economic changes. So how has this critical situation affected the greed in all age people and their assessment of the greed in others? The following methods were used in the study: correlation, comparative and qualitative analysis of the results obtained by the method of semantic differential, incomplete sentences, situational tasks and the author’s method of determining greed. As a result, it is shown that young people more often than adults consider greed as a personality trait inherent in everyone. Adult subjects to a greater extent equate the greed for experiencing negative emotions - evil, fear and aggression. In both groups, greed is defined as own limitation that prevents one from enjoying a full life, but through greed you can control your expenses, save and be responsible for your consumer behavior. Researchers of young and mature age believe that the greed of others limits their ability to live comfortably, satisfy their desires, achieve goals and live in abundance. Young and adult people’s assessment of their own greed and the greed of others is moderate. Self-assessment of own greed and assessment of the greed of family and friends are similar. The assessment of city and country leader’s greed is higher than their own assessment of greed.